Effect of total methanolic extract of Phytolacca decandra L. on electrophysiological properties of AV node in male rat heart - A Hadjiakhoondi; M Naeebpoor; MR Verdiyan-rizi; Y Ashrafiyan (Institue of Medicinal Plants, ACECR, 2003)
Subject of this study was the evaluation of effect of the total methanolic extract of Phytolacca decandra L. on isolated male rat heart and specialy effect of this extract on electrophysiological properties of AV node. Male rat heart after isolation was infused with Tyrode solution (Longendorfe method) and with electrophysical methods, all heart electrical parameters for example record from atrium and ventricle, measurment of myocardial contraction force and conduction rate in AV node were done. Various protocols for measurment of AV node recovery kinetic, AV conduction time ERP and wenckebach cycle length in presence and absence of extract were done for studing effects of the extract and finding the mechanism of them. The result of this study show that the methanolic of Phytolacca decandra L. in a dose dependent model via effect on basic and functional parameters has depressed these parameters and this plant can be useful in supraventricular arrhytmias.